Beaking eyes: a rare presentation - Barki, Renuka; Channagiri, Anu Sheshadri; Nitture, Pradeep (International Journal of Research in Medical Sciences, 2024)
As the ocular globes grow and develop, their shapes evolve from asymmetric, elongated, or conical to a nearly spherical, elliptical morphology. We see such morphological changes around the globe in adults with a few of the pathological conditions. Here is a 51-year-old male with an incidental finding of posterior beaking of the right eyeball on an MRI of the brain. Tilting of the disc was noted on the fundus examination, no clinical findings were relevant to any pathology. So, can this be a normal physiological variance?